Student companion to Richard Wright - Felgar, Robert, 1944- (Student companions to classic writers., 2000)
"Born in rural Mississippi, the grandson of slaves, Richard Wright overcame daunting obstacles to achieve literary recognition as the creator of some of America's most powerful black literature. Wright's works changed the cultural landscape by challenging old stereotypes and myths about race. This critical volume helps students appreciate the literary significance of such groundbreaking works as Native Son and the autobiographical Black Boy. It serves students of both literature and social history as it explores the themes of racism and all types of institutionalized oppression that Wright exposed in his writing."--Jacket